EMOTIONAL INTELLIGENCE AS A FACTOR IN THE DEVELOPMENT OF LEADERSHIP QUALITIES IN HIGH SCHOOL STUDENTS - Хоменко-Семенова, Леся; Кокарєва, Анжеліка; Бондар, Мілана; Рожківський, Андрій (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article updates the problem of psychological readiness of modern youth for leadership in conditions of high social turbulence and martial law in Ukraine. It is emphasized that today society requires not authoritarian managers, but emotionally mature leaders capable of self-regulation and empathetic interaction. The aim of the work is the theoretical substantiation and empirical study of emotional intelligence as a fundamental factor determining the development of leadership qualities in adolescence. The empirical research was implemented at Dubno Lyceum No. 1 in the Rivne region, involving 40 students of grades 9–11. The diagnostic toolkit included the following methods: «Diagnosis of Leadership Abilities» (E. Zharikov, E. Krushelnytskyi), «Diagnosis of Emotional Intelligence» (N. Hall), and «Motivation for Success and Fear of Failure» (A. Rean). The results of the study revealed a significant dissonance between the leadership potential and the actual level of development of leadership qualities in high school students. It was established that 72.5% of respondents possess a sufficient (medium) level of natural leadership potential, and 45% have high motivation for achieving success. However, the realization of this potential is blocked by a low level of formed leadership skills (in 60% of students). It is proven that the key reason for this gap is a deficit in emotional intelligence: 72.5% of the sample demonstrate a low integrative EQ indicator. The most critical areas were identified as «managing one’s own emotions» (low level in 80% of students) and «recognizing the emotions of others» (low level in 57.5%). It is concluded that low emotional competence acts as a restraining factor that prevents motivated adolescents from transforming their potential into actual leadership behavior. The necessity of introducing training programs into the educational process, aimed primarily at developing skills of emotional self-regulation and social perception, is substantiated.